FAULT CREEP GROWTH MODEL AND ITS RELATIONSHIP WITH OCCURRENCE OF EARTHQUAKES - Chen Z.; Bai W. (My University, 2006)
A fault model is used to analyse creep growth process of microcracks in damage zone near the tips of fault by means of the rheology fracture mechanics. When microcracks in the zone link each other and their deformation quickly intensifies, it means that an earthquake is taking place to a certain degree. The relationships among some key parameters that are correlated to the growth of microcracks are analysed theoretically. These parameters include failure time of fault, number of microcracks in unit area, stresses field, yield strength and rheological properties of medium. The results indicate that the model proposed here is reasonable to describe the pregnant process of an earthquake. In the meantime, this research shows that, with the results of in situ surveys and lab experiments, it is possible to estimate the time span for a fault expanding. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CREEP; EARTHQUAKE; FAULT; GROWTH; MICROCRACK; MODEL